"American" or "Multiethnic"? Family Ethnic Identity Among Transracial Adoptive Families, Ethnic‐Racial Socialization, and Children's Self‐Perception. Issue 150 (December 2015) - Pinderhughes, Ellen E.; Zhang, Xian; Agerbak, Susanne
Abstract: Drawing on a model of ethnic‐racial socialization (E‐RS; Pinderhughes, 2013), this study examined hypothesized relations among parents' role variables (family ethnic identity and acknowledgment of cultural and racial differences), cultural socialization (CS) behaviors, and children's self‐perceptions (ethnic self‐label and feelings about self‐label). The sample comprised 44 U.S.‐based parents and their daughters ages 6 to 9 who were adopted from China. Correlation analyses revealed that parents' role variables and CS behaviors were related, and children's ethnic self‐label was related to family ethnic identity and CS behaviors. Qualitative analyses point to complexities in children's ethnic identity and between family and children's ethnic identities. Together, these findings provide support for the theoretical model and suggest that although ethnic identity among international transracial adoptees (ITRAs) has similarities to that of nonadopted ethnic minority children, their internal experiences are more complex.